Effects of the “Active Communication Education” Program on Hearing-Related Quality of Life in a Group of Italian Older Adults Cochlear Implant Users - Giallini, Ilaria; Nicastri, Maria; Inguscio, Bianca M. S.; Portanova, Ginevra; Magliulo, Giuseppe; Greco, Antonio; Mancini, Patrizia (Frontiers in Psychology, 2022)
Introduction The present study aimed to evaluate the effects of the Active Communication Education (ACE) program on the social/emotional impacts of hearing loss (HL) in a group of older adults with a cochlear implant (CI). Design Prospective cohort study design, with a “within-subject” control procedure. Study Sample Twenty adults over-65 post-lingually deafened CI users. All subjects were required to be native Italian speakers, to have normal cognitive level, have no significant psychiatric conditions and/or diagnosed incident dementia, and used CI for at least 9 months. Materials and Methods Twenty participants were assessed using the Hearing Handicap Inventory for the Elderly (HHIE), the Geriatric Depression Scale (GDS), and the Speech, Spatial, and Qualities of Hearing Scale (SSQ) before, during, and after ACE program, with a one and 6-month follow up. The cognitive and audiological evaluation was carried out before commencing the ACE program. Results The ACE program had a positive impact by reducing HL’s social/emotional effects. Participants benefited from a rehabilitative approach by improving multilevel skills: comprehension of audiological and hearing dimensions, acquisition of communicative, pragmatic and problem-solving strategies, and interaction and sharing of experiences with peers. Conclusion Although targeting the older adults with moderate HL, the ACE program also seemed to benefit older adult CI users. An improvement in social and emotional adaptation to hearing difficulties can, in turn, significantly promote optimal use of CI in the older adults, thereby possibly reducing the risk of losing motivation and engagement in device use and in rehabilitation protocols.